1999
DOI: 10.1063/1.370170
|View full text |Cite
|
Sign up to set email alerts
|

Negative magnetoresistance and impurity band conduction in an In0.53Ga0.47As/InP heterostructure

Abstract: The electrical conduction in an n-type In0.53Ga0.47As/InP sample grown by molecular beam epitaxy has been analyzed in the magnetic field up to 1.5 T, at temperatures from 15 to 295 K. The electrical conduction has been ascribed to the impurity band (IB), located in the interface between the epilayer InGaAs and the substrate InP. The contribution of the conduction band electrons in bulk InGaAs layer to the electrical conduction was negligible. The IB conduction was almost metallic. We observed within the IB two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 52 publications
1
8
0
Order By: Relevance
“…1b we can see a small negative magnetoresistance in low magnetic field at temperatures below 59 K. Negative magnetoresistance has been widely observed in many semiconductors and magnetic materials [1,25,26].…”
Section: Preparation Of the Sample And Measurementsmentioning
confidence: 74%
See 4 more Smart Citations
“…1b we can see a small negative magnetoresistance in low magnetic field at temperatures below 59 K. Negative magnetoresistance has been widely observed in many semiconductors and magnetic materials [1,25,26].…”
Section: Preparation Of the Sample And Measurementsmentioning
confidence: 74%
“…In general, in the impurity band, the mobility of carriers is proportional to the concentration of structure defects producing impurity band states. From comparison of the mobility of impurity band carriers in m0.53 Ga0 4 7Αs/ΙnΡ (0.3 m 2 /(V s)) [1] and InAs/GaAs (0.8 m 2 /(V s)) heterostructures it can be concluded that the concentration of structure defects which form the impurity band is higher in the InAs/GaAs heterostructure. This is consistent with our assumption of a significant contribution of dislocations to the density of states in the impurity band in both heterostructures.…”
Section: Comments On the Electrica1 Conduction In Inas/gaasmentioning
confidence: 99%
See 3 more Smart Citations